Comparison between Covid-19 and influenza A(H1N1) pandemic experiences and risk perception in Mexican university - Ingris Peláez-Ballestas; Claudia Infante-Castañeda; Liliana Giraldo-Rodríguez (Instituto Nacional de Salud Pública, 2021)
Objective. To compare the perceptions and experiences between the A(H1N1) and Covid-19 pandemics in a university population. Materials and methods. Online surveys were administered during the influenza A(H1N1) -originated in Mexico in 2009- and Covid-19 epidemics. Measures: sociodemographic characteristics, knowledge, information and communication, perception of risk, physical and mental health, effects on daily life, and preventive behaviors. Results. This study included 24 998 respondents, 51.36% from the A(H1N1) group and 48.63% from the Covid-19 group. Differences were observed in the perception of severity. During the influenza A(H1N1) pandemic worry was the feeling reported most frequently, while for Covid-19 it was anxiety. Covid-19 had greater impact on students' family economy and caused a higher uncertainty. Conclusions. The perceptions and experiences of the two pandemics were similar but the impact has been much greater for Covid-19, especially in terms of the severity, family economy, preventive behaviors, and uncertainty